Movimento da luta antimanicomial: trajetória, avanços e desafios - Barbosa, Guilherme Correa [UNESP]; Costa, Tatiana Garcia da; Moreno, Vania [UNESP] (My University, 2012)
This article aims to address the trajectory of anti-asylum fight movement, presenting some of their actions developed to change social imagery about madness. Its initiatives aim to bring awareness of the population to the disrespectful situations undergone by patients with mental disorders, whether in society or in mental health care. It should be noted, however, the fact that this movement has not yet been institunalized. Thus, among among its hardest challenges are the need of mental health professionals to rediscover their history and respect its trajectory as well as users recognizing the importance of partnership and the need for the presence of mental health professionals as mediators of the ongoing process. Thus, the text analysis the fact that users, family and workers should be protagonists of a new form of care in mental health.

O presente artigo tem por objetivo abordar a trajetória do movimento da luta antimanicomial, apresentando algumas das ações por ele desenvolvidas a fim de transformar o imaginário social sobre a loucura. Suas iniciativas almejam trazer à consciência da população as situações de desrespeito às quais são submetidos os portadores de transtorno mental, quer no convívio com a sociedade, quer na atenção à saúde mental. Ressalte-se, porém, o fato de que esse movimento ainda não se tenha institucionalizado. Deste modo, dentre seus maiores desafios estão a necessidade de os profissionais de saúde mental redescobrirem sua história e respeitarem sua trajetória, bem como dos usuários reconhecem a importância da parceria e da necessidade da presença dos técnicos de saúde mental como mediadores do processo em construção. Assim, o texto analisa o fato de que usuários, familiares e trabalhadores devem ser os protagonistas de uma nova forma de cuidado em saúde mental.
The anti-asylum fight movement: trajectory, progress and challenges
Keywords: Anti-asylum fight; Struggle for recognition; Social movement; Antimanicomial; Luta por reconhecimento; Movimento social